The Cultural Heritage of Psychiatry and Its Literary Transformations : Middle Ages to the Present - Röder, Katrin; Wächter, Cornelia (Literature and Cultural Studies E-Books Online, Collection 2026., 2025)
This volume investigates the role of English, British, Irish, American, Canadian and Nigerian anglophone literary conceptualizations of mental and social distress, its diagnosis and treatment as transformative parts of the cultural heritage of psychiatry. Demonstrating that the history of psychiatry is not a narrative of unbridled, unequivocal progress, the volume explores how literary texts negotiate and critique dominant and alternative forms and traditions of treatment and care, how they challenge the medicalization of non-normative thoughts and behaviour and how they bear witness to and fragmentarily retrieve and imagine suppressed voices, thereby producing counter-cultural memories.